PRODUCT AND PROCESS DESIGN PRINCIPLES: SYNTHESIS, ANALYSIS AND EVALUATION - Seider, Warren D. 200621; Lewin, Daniel R. 403708; Seader, J.D. 206687; Widagdo, Soemantri; Rafiqul Gani; Ng, Ka Ming (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
Includes bibliographical and references